Antimicrobial resistance in integrated agroecosystems: State of the science and future opportunities. Issue 6 (3rd October 2021) - Howe, Adina C.; Soupir, Michelle L.
Abstract: As the Journal of Environmental Quality (JEQ) celebrates 50 years of publication, the division of environmental microbiology is one of the newest additions to the journal. During this time, significant advances in understanding of the interconnected microbial community and impact of the microbiome on natural and designed environmental systems have occurred. In this review, we highlight the intractable challenge of antimicrobial resistance (AMR) on humans, animals, and the environment, with particular emphasis on the role of integrated agroecosystems and by highlighting contributions published in JEQ. From early studies of phenotypic resistance of indicator organisms in waters systems to current calls for integrating AMR assessment across "One Health, " publications in JEQ have advanced our understanding of AMR. As we reflect on the state of the science, we emphasize future opportunities. First, integration of phenotypic and molecular tools for assessing environmental spread of AMR and human health risk continues to be an urgent research need for a one health approach to AMR. Second, monitoring AMR levels in manure is recommended to understand inputs and potential spread through agroecosystems. Third, baseline knowledge of AMR levels is important to realize the impact of manure inputs on water quality and public health risk; this can be achieved through background monitoring or identifying the source‐related genes or organisms. And finally, conservation practices designed to meet nutrient reduction goals should be explored for AMR reduction potential. Core Ideas: Phenotypic and molecular tools are needed to assess environmental spread of antimicrobial resistance (AMR). Monitoring AMR in manure is recommended to understand inputs to agroecosystems. For environmental monitoring, it is important to measure baseline levels of AMR. Identify source‐related genes or conduct background monitoring to assess baseline AMR. Conservation practices can be co‐managed for nutrient and AMR reduction.